Analisis Kemampuan Literasi Informasi Mahasiswa Program Studi Pendidikan Bahasa Arab Universitas Islam Negeri Maulana Malik Ibrahim Malang dalam Mengerjakan Tugas Makalah Menggunakan Model Literasi Informasi The Big Six - Afiyani, Aqilah Dzira; Alfariza, Rahma Devianti (LIBTECH: LIBRARY AND INFORMATION SCIENCE JOURNAL, 2023)
This study aims to determine the information literacy skills possessed by students of the Arabic Language Education Study Program in working on paper assignments. The information literacy model used is The Big Six which consists of six stages, including Task Definition, Information Seeking Strategies, Location and Access, Use of Information, Sythesis, and Evaluation. Information literacy is the ability to find information needs, including understanding how libraries are organized, the ability to evaluate information content and use it effectively. The importance of information literacy skills that must be possessed by each individual in order to be able to be more critical of the information they get. The research method used is a qualitative approach through descriptive research methods. The data collection technique used is interview. The selection of informants was carried out using purposive sampling technique, namely sampling using certain considerations in accordance with the desired criteria to be able to determine the number of samples to be studied. In this study, the author interviewed 5 informants, who are students of the Arabic Language Education Study Program at UIN Maulana Malik Ibrahim Malang. The five students named Addini, Elfina, Uswatun, Icha, and Laila. The results obtained from this study are that the students studied have quite good information literacy skills in working on paper assignments with several indicators such as determining the topic, determining the information needed, determining relevant and accurate sources of information, determining the location of information sources, accessing information, utilizing information, utilizing reference manager, presenting information into several formats and evaluating the process in terms of efficiency and effectiveness. Keywords: Information literacy; Literacy Skills; The Big Six